2006
DOI: 10.1158/1078-0432.ccr-06-0712
|View full text |Cite
|
Sign up to set email alerts
|

A Homeobox Protein, Prox1, Is Involved in the Differentiation, Proliferation, and Prognosis in Hepatocellular Carcinoma

Abstract: Purpose: It has been shown that a lymphatic differentiation master gene, prox1, also plays an essential role in fetal hepatocyte migration. Its expression is detected in embryonic hepatoblasts and in adult hepatocytes. Hepatoma cells are similar to embryonic hepatoblasts to a certain extent because they both proliferate and invade the surrounding tissue. To address the possibility that Prox1 may be involved in the tumorigenesis of hepatocellular carcinoma (HCC), human clinical samples were analyzed. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 15 publications
3
95
1
6
Order By: Relevance
“…Recent studies demonstrated that reduction of Prox1 was found in HCC tissues and low expression of Prox1 was associated with poor prognosis and un-differentiation status. 24,25 These data implicate a potential tumor suppressor role of Prox1 in HCC. However, the underlying mechanism by which Prox1 inhibits the development of HCC is unknown.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Recent studies demonstrated that reduction of Prox1 was found in HCC tissues and low expression of Prox1 was associated with poor prognosis and un-differentiation status. 24,25 These data implicate a potential tumor suppressor role of Prox1 in HCC. However, the underlying mechanism by which Prox1 inhibits the development of HCC is unknown.…”
Section: Introductionmentioning
confidence: 71%
“…The study of functional role of Prox1 in HCC was first reported by Shimoda et al 24 They showed that Prox1 expression was associated with the differentiation status of HCC tumors. Figure 5A, Twist reversed the increase of β-galactosidase-positive cells induced by Prox1.…”
Section: Prox1 Inhibits Proliferation Of Hcc Cells By Inducingmentioning
confidence: 99%
“…14,33,34 Decreased PROX1 expression has been found in several cancers, including hepatocellular carcinoma, biliary duct cancer, and breast cancer. [35][36][37] However, in colon cancer, overexpression of PROX1 induces colon cancer progression by promoting a transition from a benign to a highly dysplastic phenotype. 38 In cervical cancer, PROX1 lies within a region of amplification (chromosome 1q) which could suggest that PROX1 copy number gain may function similarly to that in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PROX1 plays multifunctional roles in human cancers and acts as a tumor suppressor gene or an oncogene based on the cancer type, thus exerting variable effects on cell proliferation and differentiation [8]. Decreased expression of PROX1 is observed in pancreatic cancers, hepatocellular carcinomas, sporadic breast cancers, and biliary carcinomas, indicating that PROX1 plays a tumor-suppressive role in these cancers [9][10][11][12]. In contrast, overexpression of PROX1 is observed in colorectal cancers, endothelial tumors, and gliomas, indicating that PROX1 promotes the progression of these cancers [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%